Water and the Law - Salvestrini, Francesco (Archaeopress Publishing, 2024)
Water and the Law investigates water resource law in the statutory legislation codified by commune, oligarchic and seigneurial governments of cities and smaller municipalities in Northern and Central Italy from the thirteenth to the fourteenth centuries. It aims to shed light on the relationship between water management norms and the local environment, that is how urban governments planned the use and distribution of water, and the protection of inhabited areas from the danger of flooding. Through a careful analysis of just two hundred statutory regulations that deal with water resources, the text compares the solutions adopted in Northern Italy, presenting a relatively large water supply and a dense network of tributaries of the river Po, with the situation in central areas of the peninsula (including Rome), where smaller watercourses with torrential characteristics - such as the Arno and the Tiber - interact with important cities and manufacturing centres like Florence. From this point of view, the book highlights the existence of a border between Continental Italy (north of the Tuscan-Emilian and Tuscany-Romagna Apennines) and the Peninsular Italy (south of it). In fact, when it came to building the necessary infrastructure for the supply of water and its distribution for irrigation purposes, municipal authorities in the Po area made provision for private-sector initiatives, whereas in the central regions of the country, such initiatives were largely the result of public works and projects pursued by the Popular governments at the helm of numerous cities. Lastly, the text relativises the awareness of legislators concerning the health and hygiene risks associated with the use and improper disposal of polluted and infected water, preferring to speak about a normative defence of the semantically broader category of decorum.